Finance and Development, September 1966. (Finance and Development; Finance and Development ;, 1966)
This paper reviews the development of Iran under the IMF's assistance. Iran has made considerable use of the IMF's resources. It joined the IMF in 1945 with an original quota of USD 25 million. The quota has been periodically raised and this year reached USD 125 million. Total purchases from the IMF by Iran have amounted to USD 121 million, and repurchases now total USD 107 million, the last transaction being a repurchase of USD 3.5 million in July 1965. The World Bank has lent more to Iran than anywhere else in the Middle East.